Mental health, stigma, and neglected tropical diseases: A review and systematic mapping of the evidence - Koschorke, Mirja; Al-Haboubi, Yasmin Hussain; Tseng, Po-Chang; Semrau, Maya; Eaton, Julian (Frontiers in Tropical Diseases, 2022)
Recent years have seen an increase in recognition of the important impact that mental health, wellbeing, and stigma have on the quality of life of people affected by neglected tropical diseases (NTDs), including the publication of global normative guidance and policy frameworks. However, systematic collation of the evidence that can guide greater clarity of thinking for research and practical application of effective interventions is lacking. We used systematic mapping methodology to review the state of the evidence around mental health, stigma, and NTDs in low- and middle-income countries, applying a simple theoretical framework to explore intersections between these areas. We built on existing reviews on the links between each domain, bringing the reviews up to date, across the NTDs identified by the WHO (minus recent additions). After systematic searching of major databases, and exclusions, we identified 190 papers. Data extraction was done to inform key topics of interest, namely, the burden of mental distress and illness/stigma associated with NTDs, the mechanisms by which NTDs add to mental distress and illness/stigma, how mental distress and illness/stigma affect the outcome and treatment of NTDs, and efficacy of interventions to address these domains. We also document the recommendations given by the authors of included studies for research and interventions. We found that there has been a substantial increase in research, which remains very heterogeneous. It was dominated by skin conditions, especially leprosy and, less so, lymphatic filariasis. Few studies had a comparative and even fewer had an intervention design. Our findings were however consistent with existing reviews, pointing to a high prevalence of mental conditions, substantially mediated by stigma and exclusion and a lack of sufficient access to support for mental wellbeing in programmes, despite the existence of effective interventions. These interventions cut across mental health services, stigma reduction, community engagement, and empowerment of people affected. We conclude that the evidence justifies increased investment in practical and integrated interventions to support the wellbeing of people affected by NTDs but that there remains a need for implementation research of consistent quality, and basic science around the impact of mental health interventions on NTD outcomes (including on elimination efforts) needs to be strengthened.